Age-dependent phenotypic modulation of smooth muscle cells in the normal ascending aorta - Balint, Brittany; Bernstorff, Inés García Lascurain; Schwab, Tanja; Schäfers, Hans-Joachim (Frontiers in Cardiovascular Medicine, 2023)
Objectives Ascending aortic aneurysms are associated with pre-existing conditions, including connective tissue disorders (i.e., Marfan syndrome) and bicuspid aortic valves. The underlying mechanisms remain uncertain. Even less is known regarding ascending aortic aneurysms in individuals with normal (i.e., tricuspid) aortic valves (TAV), and without known aneurysm-associated disorders. Regardless of etiology, the risk of aortic complications increases with biological age. Phenotypic modulation of smooth muscle cells (SMCs) is a feature of ascending aortic aneurysms, whereby contractile SMCs are replaced with synthetic SMCs that are capable of degrading the aortic wall. We asked whether age itself causes dysfunctional SMC phenotype modulation, independent of aortic dilatation or pre-existing aneurysm-associated diseases. Methods Non-dilated ascending aortic samples were obtained intra-operatively from 40 patients undergoing aortic valve surgery (range: 20–82 years old, mean: 59.1 ± 15.2). Patients with known genetic diseases or aortic valve malformations were excluded. Tissue was divided, and a portion was formalin-fixed and immunolabeled for alpha-smooth muscle actin (ASMA), a contractile SMC protein, and markers of synthetic (vimentin) or senescent (p16/p21) SMCs. Another fragment was used for SMC isolation (n = 10). Cultured SMCs were fixed at cell passage 2 and stained for phenotype markers, or were cultured indefinitely to determine replicative capacity. Results In whole tissue, ASMA decreased (R2 = 0.47, P < 0.0001), while vimentin increased (R2 = 0.33, P = 0.02) with age. In cultured SMCs, ASMA decreased (R2 = 0.35, P = 0.03) and vimentin increased (R2 = 0.25, P = 0.04) with age. p16 (R2 = 0.34, P = 0.02) and p21 (R2 = 0.29, P = 0.007) also increased with age in SMCs. Furthermore, the replicative capacity of SMCs from older patients was decreased compared to that of younger patients (P = 0.03). Conclusion By investigating non-dilated aortic samples from individuals with normal TAVs, we found that age itself has a negative impact on SMCs in the ascending aortic wall, whereby SMCs switched from the contractile phenotype to maladaptive synthetic or senescent states with increased age. Therefore, based on our findings, modification of SMC phenotype should be studied as a therapeutic consideration against aneurysms in the future, regardless of etiology.